Drug-Resistant Pulmonary Tuberculosis - Putri, Olivia; Salim, Megan Angelita; Gunawan, Aileen; Devin, Devin; Amaris, Ezrela; Alexander, David; Kevin, Gregorius; Febriana, Gabriella Gita (Indonesian Journal of Life Sciences, 2023)
Tuberculosis (TB) caused by the pathogenic bacteria Mycobacterium tuberculosis (MTb) still remains a highly prevalent disease, particularly in low and middle-income countries. Due to the bacteria’s atypical cell wall structure, ability to form granuloma, and capacity to switch between replicating and non-replicating states in the host lung parenchyma, the fundamental treatment of patients diagnosed with TB involves a 6-month long daily drug administration. With Indonesia ranking among the nations with the highest TB burden worldwide, there has been an alarming increase of drug-resistant MTb (DR-MTb) strains all over the country in recent years. However, there are currently limited studies available that highlight MTb resistance profiles across different regions within Indonesia. The major risk factors contributing to the emergence and spread of TB in Indonesia include health conditions, environmental conditions, and socioeconomic status. Furthermore, natural compounds and drug repurposing can be employed to combat the further spread of DR-MTb strains across the country, especially in rural regions.